2020
DOI: 10.1016/j.psj.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Lack of access to an open water source for bathing inhibited the development of the preen gland and preening behavior in Sanshui White ducks

Abstract: As a species of waterfowl, ducks rely on access to water to facilitate feeding behaviors. Further, wet preening behavior in ducks relies on access to water and is a key behavior for duck welfare. Traditionally, Chinese duck farms provide not only free access to drinking water in the duck house but also an open water pool outside of the house. However, recent restrictions prohibit the use of an open water pool for raising ducks in some areas of China. Little is known about the effects of not providing an open w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The differences between wet and dry preening have not been extensively evaluated for domesticated dabbling ducks. A single preliminary study of Sanshui White ducks, featuring one replicate flock per treatment, linked access to swimming water with the preening gland development (gland size and weight, and % oil weight by gland size; Mi et al, 2020 ). However, research from other avian species suggests that functional and motivational differences could exist.…”
Section: Duck Welfare In Relation To the Housing Environmentmentioning
confidence: 99%
“…The differences between wet and dry preening have not been extensively evaluated for domesticated dabbling ducks. A single preliminary study of Sanshui White ducks, featuring one replicate flock per treatment, linked access to swimming water with the preening gland development (gland size and weight, and % oil weight by gland size; Mi et al, 2020 ). However, research from other avian species suggests that functional and motivational differences could exist.…”
Section: Duck Welfare In Relation To the Housing Environmentmentioning
confidence: 99%
“…Being semi-aquatic, ducks' feather condition is particularly critical for maintaining water repellence which ensures protection and buoyancy when in the water. When provided the opportunity, domestic ducks will utilize water for swimming, ducking and diving, head dipping and tossing, dabbling, wing rubbing, resting in or near water, and wet preening (Miller, 1977;Rodenburg et al, 2005;Jones et al, 2009;Waitt et al, 2009;Liste et al, 2012a;Mi et al, 2020). Wet preening is a maintenance behavior that relies on water access.…”
Section: Bathing and Preening Behaviorsmentioning
confidence: 99%
“…The preen gland is a pear-shaped bilobed holocrine gland located near the base of a duck's tail, which secretes glycolipids (ALjalaud, 2013;Mohamed, 2019). The gland is thought to contribute to maintaining the flexibility and water-repellent nature of a duck's feathers due to the gland's hydrophobic secretions (Mi et al, 2020). It may also play a role in protecting against bacterial and fungal infections, as well as contributing to thermoregulation, pheromone production, and hormone (e.g., prostaglandin and growth) production (Hassanin et al, 2021).…”
Section: Bathing and Preening Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Mi et al found that providing an open water source for bathing can promote the development of the uropygial gland and preening behavior in ducks [ 27 ]. However, there is no report about the effect of the rearing systems on the metabolic content within the uropygial gland.…”
Section: Introductionmentioning
confidence: 99%